Reasons for UPorto (Portugal) students choose the teaching profession and their perceptions of it (Práxis Educativa, 2024)
The study presented aimed to understand what attracts Portuguese students to choose the teaching profession. The application of the Fit Choice questionnaire to the entire student body of teacher training courses at the University of Porto, in 2023-2024, revealed results such as: the primary reason for choosing the profession is the passion for the field of study, followed by the contribution to society and the future of children and adolescents, and the love for teaching. The surveyed students are motivated for the profession, although they consider it challenging, demanding (in terms of specialized knowledge and work), and offering limited rewards (both financial and social); they are delighted with their choice, despite many having been dissuaded and encouraged to choose another profession. In the current context of teacher shortages, this knowledge can inform education policies and strategies for recruiting new candidates to the teaching profession.Keywords: Teaching attractiveness. Initial teacher education. Perceptions of the teaching profession.